An assessment of the management of anaemia in acute care settings in the United Kingdom: The value of a collaborative approach. Issue 5 (30th May 2021) - Rampotas, Alexandros; Prodger, Catherine F.; Murphy, Michael F.
Abstract: Objectives: Patients presenting to acute care settings with anaemia are at risk of inadequate investigation and inappropriate blood transfusion. In collaboration with Haematology Specialty Trainee Audit and Research (HaemSTAR), this study set out to assess current red blood cell (RBC) transfusion practice and anaemia management in acute care settings across the United Kingdom. Methods and Results: Fifteen different hospitals participated in the study over a period of a month beginning 01 January 2020. Eight‐hundred and twenty‐eight eligible patients presenting to acute care settings with anaemia received RBC transfusions during this period. Of these, 159 (19.2%) received inappropriate transfusions according to National Institute for Health and Care Excellence guidelines, and 257 (31%) could have been treated with alternatives to transfusion. One‐hundred and fifty‐four (18.6%) did not have a cause for their anaemia identified by the time they were discharged from hospital, and in over 50% of these cases that was because of inadequate investigation with blood tests, specialist investigation or referral, or both. Conclusion: This study found that the appropriateness of transfusion and investigation of anaemia in acute care settings warrant improvement and also demonstrates the value of HaemSTAR in facilitating time‐efficient collection of high‐quality data.